Ancient Plant DNA as a Window Into the Cultural Heritage and Biodiversity of Our Food System - Przelomska, Natalia A. S.; Armstrong, Chelsey G.; Kistler, Logan (Frontiers in Ecology and Evolution, 2020)
Since the beginning of the ancient DNA revolution in the 1980s, archaeological plant remains and herbarium specimens have been analysed with molecular techniques to probe the evolutionary interface of plants and humans. In tandem with archaeobotany, ethnobiology, and other methods, ancient DNA offers tremendous insights into the co-evolution of people and plants, and the modern genomic era offers increasingly nuanced perspectives on plant use through time. Meanwhile, our global food system faces threats linked with declining biodiversity, an uncertain climate future, and vulnerable crop¬–wild relatives. Ancient plant DNA does not yield easy answers to these complex challenges, but we discuss how it can play an important role in ongoing conversations about resilience, sustainability, and sovereignty in our food system.